2019
DOI: 10.1007/s42452-019-0401-z
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the effect of SiC particles in machining process of Al–5.3%CU-SiCp–Al2O3p hybrid nanocomposite by EDM

Abstract: In this study, the EDM process was used to investigate the machining properties of Al-5.3% CU-SiC p -Al 2 O 3p aluminum composite, including SR, MRR, and TWR. Input parameters consist of two electrical and non-electrical category which relates to EDM settings and the composite variables including volume fraction and size of silicon carbide particles in nano and micro scale. SEM and TEM were used to investigate particles and the base metal. Surface roughness measurement device and ball milling was used to measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In the TWR's main effect plot, increasing the percent Sic nano particles in Al-based hybrid composite from 3 to 4.5 improves TWR, and then a dip is observed as shown in Figure 23. Shabgard et al [6] also discovered that increasing the reinforcing particles increases TWR. The increase in SiC particles will increase contamination and act as a barrier to electron movement between tool and workpiece.…”
Section: Effect Of Percent Sic Nano In Al-based Hybrid Compositementioning
confidence: 95%
See 2 more Smart Citations
“…In the TWR's main effect plot, increasing the percent Sic nano particles in Al-based hybrid composite from 3 to 4.5 improves TWR, and then a dip is observed as shown in Figure 23. Shabgard et al [6] also discovered that increasing the reinforcing particles increases TWR. The increase in SiC particles will increase contamination and act as a barrier to electron movement between tool and workpiece.…”
Section: Effect Of Percent Sic Nano In Al-based Hybrid Compositementioning
confidence: 95%
“…The main effect plot of SR for experiment revealed that increasing the percent SiC nano particles in Al-based hybrid composite result in a decrease in SR from 3 percent to 4.5 percent, followed by an increase at 6 percent with the worst SR at 6 percent as shown in Figure 24. According to Shabgard et al [6] increasing the fraction of reinforcing particles in hybrid composite results in an increase in SR. Since SiC particles are ejected as solid when enough energy is provided due to their high melting point, the vacant space of each reinforcing particle will persist as a spot on the specimen's surface as shown in Figure 28.…”
Section: Effect Of Percent Sic Nano In Al-based Hybrid Compositementioning
confidence: 99%
See 1 more Smart Citation
“…For higher values of pulse on time, MRR and SR increased, whereas TWR decreased. 163 Jadam et al 164 studied the effect of peak current on MRR. As the peak current was increased, MRR increased for both conventional EDM and PMEDM as when peak current was increased; higher intensity sparks were generated.…”
Section: Surface Characteristicsmentioning
confidence: 99%